High-Performance Dielectric Modulated Epitaxial Tunnel Layer Tunnel FET for Label-Free Detection of Biomolecules - Kunal Aggarwal; Avinash Lahgere (IEEE Open Journal of Nanotechnology)
In this paper, using calibrated simulation we have reported a dielectric modulated epitaxial tunnel layer TFET (DM ETL-TFET) for the label-free detection of biomolecules. We have shown that due to vertical tunneling direction, the ETL-TFET exhibits $\sim$ 3 orders of improvement in the ON-state current in comparison to its counterpart conventional TFET. In addition, the proposed DM ETL-TFET biosensor shows $\sim$ 4 orders, and $\sim$ 1 order higher ON-state current sensitivity than the past reported core-shell junctionless NT-TFET, and DM NT-TFET biosensors, respectively. Moreover, in comparison to the lateral DM TFET, the proposed DM ETL-TFET shows $\sim$ 310 mV higher threshold voltage sensitivity. Also, the subthreshold swing sensitivity of the proposed biosensor is found to be $\sim$ 0.63 for the keratin biomolecule. Although the proposed biosensor shows almost the same selectivity, the proposed DM ETL-TFET biosensor does not need a complex fabrication process flow, hence, reducing the fabrication cost. Our findings that the proposed biosensor is a lucrative alternative to the FET-based biosensors.